La esquina confluente (2020)
The confluent corner is an urban renovation project which aims to revitalize the ¿Capuchina? Neighborhood in Bogotá, Colombia. The project consists of transforming the site by building a 22-story tower which holds different types of commerce and offices and leaves room for creating a very green and comfortable firs floor for the city. The project is surrounded by important avenues such as the Caracas and Calle 19. The question that guided this project was the following: What type of urban gestures are fundamental for improving a community's quality of life and guarantee the economic development of the neighborhood at the same time? This was the result of observing a lack of green areas and the projection of the ¿Metro de Bogotá? which is why there is a search for integrating both realities into one cohesive urban solution. With these decisions, the quality of life would improve due to the increase of commercial activity bringing a sense of security as well as more economic development to the neighborhood, in addition to the improvement of public space with the green areas and small parks.